2014
DOI: 10.1098/rspb.2014.0661
|View full text |Cite
|
Sign up to set email alerts
|

Hox gene duplications correlate with posterior heteronomy in scorpions

Abstract: The evolutionary success of the largest animal phylum, Arthropoda, has been attributed to tagmatization, the coordinated evolution of adjacent metameres to form morphologically and functionally distinct segmental regions called tagmata. Specification of regional identity is regulated by the Hox genes, of which 10 are inferred to be present in the ancestor of arthropods. With six different posterior segmental identities divided into two tagmata, the bauplan of scorpions is the most heteronomous within Chelicera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 45 publications
(89 reference statements)
4
116
1
1
Order By: Relevance
“…As shown in Figure 3, Figure 4 and Supplementary Files 3 and 4, the genome of the scorpion Mesobuthus martensii (Cao et al, 2013) possesses multiple copies of many of the homeobox gene families studied here. Furthermore, the spider C. salei and the scorpion C. sculpturatus also possess multiple copies of several Hox cluster genes (Schwager et al, 2007;Sharma et al, 2014a). The presence of WGD in the horseshoe crabs led us to consider whether WGD might have occurred in the chelicerate stem lineage, rather than being limited to the Xiphosura.…”
Section: Wgds In Horseshoe Crabs Chelicerates and Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3, Figure 4 and Supplementary Files 3 and 4, the genome of the scorpion Mesobuthus martensii (Cao et al, 2013) possesses multiple copies of many of the homeobox gene families studied here. Furthermore, the spider C. salei and the scorpion C. sculpturatus also possess multiple copies of several Hox cluster genes (Schwager et al, 2007;Sharma et al, 2014a). The presence of WGD in the horseshoe crabs led us to consider whether WGD might have occurred in the chelicerate stem lineage, rather than being limited to the Xiphosura.…”
Section: Wgds In Horseshoe Crabs Chelicerates and Vertebratesmentioning
confidence: 99%
“…These include the discovery of multiple copies of homeobox-containing genes in the spider Cupiennius salei (Schwager et al, 2007), the scorpion Centruroides sculpturatus (Sharma et al, 2014a) and the horseshoe crab Limulus polyphemus (Nossa et al, 2014). The latter paper showed by a variety of methods, including linkage mapping, comparison of age distribution of paralogous genes and gene cluster comparison, that WGD occurred in L. polyphemus.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the paucity of genomic resources available for Iurida, few existing datasets can presently be added to our supermatrices, and at considerable expense of matrix occupancy ( figure 3; electronic supplementary material, table S2). Adding four small datasets to our analyses (Scorpio maurus palmatus, Heterometrus petersii and two species of Scorpiops) indicated the monophyly of the genus Scorpiops with maximal nodal support, even though few genes (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) are available for the Scorpiops species; other relationships within 'Chactoidea' were not affected ( figure 3a). By contrast, addition of two scorpionids rendered the family Scorpionidae diphyletic in the best-scoring ML topology, with Scorpio maurus palmatus (represented by seven genes) nesting within the non-Liocheles hormurids (bootstrap resampling frequency of 69%; figure 3a).…”
Section: Discussion (A) a Robust Hypothesis Of Scorpion Relationshipsmentioning
confidence: 93%
“…Embryos of wild caught P. opilio and Centruroides sculpturatus were obtained as described previously [29,34]. Embryos of Limulus polyphemus were kindly provided by B. Battelle and H. J. Brockmann (Department of Biology, University of Florida) and were staged according to [35].…”
Section: Materials and Methods (A) Animal Cultivation And Gene Cloningmentioning
confidence: 99%
“…In Chelicerata, the sister group to the remaining Arthropoda, gene expression data for the Antp orthologue demonstrate conserved expression throughout the posterior tagma (opisthosoma) of multiple surveyed species, but absence from the leg-bearing prosoma [9,[27][28][29], suggesting that chelicerate Antp is not involved in appendage identity specification (figure 1b). Concordantly, functional data have demonstrated that the spider Antp orthologue represses limb development in the opisthosoma of Parasteatoda tepidariorum [30].…”
Section: Introductionmentioning
confidence: 99%